Application of Soft Computing to Address Uncertainty in Construction Project Management: A Systematic Literature Review - Setya Winarno; Sri Kusumadewi (Civil Engineering Journal, 2024)
Decision-making in Construction Project Management (CPM) involves numerous ambiguous information and uncertainties due to the nature of construction project. The Soft Computing (SC) approach, which offers several data processing strategies under uncertainty, has been extensively researched in CPM studies for decision problem solving. Decisions that cannot be adequately handled by conventional computer systems are facilitated by the SC approach. The SC approach encompasses a variety of SC techniques that are constantly developing and becoming more widely used to address real construction challenges. This study aims to conduct Systematic Literature Reviews (SLR) on the development of mainstream SC techniques and their current application in construction projects. Using an inventive SLR technique, 83 CPM papers covering the years 2018 to 2023 were selected for this study and then classified into four primary application themes of SC in CPM. The research trend was then described using bibliometric analysis. Afterwards, a topic-based qualitative analysis was conducted to investigate the application of SC approaches in the construction field. Several potential challenges to current research were then elaborated. It also contributed to suggesting future directions for the advancement of SC techniques that would be advantageous for construction research and practice. Doi: 10.28991/CEJ-2024-010-06-020 Full Text: PDF